2020
DOI: 10.2298/fuee2004631a
|View full text |Cite
|
Sign up to set email alerts
|

A new anomalous text detection approach using unsupervised methods

Abstract: Increasing size of text data in databases requires appropriate classification and analysis in order to acquire knowledge and improve the quality of decision-making in organizations. The process of discovering the hidden patterns in the data set, called data mining, requires access to quality data in order to receive a valid response from the system. Detecting and removing anomalous data is one of the pre-processing steps and cleaning data in this process. Methods for anomalous data detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the current study, the performance of our proposed algorithm was evaluated on static data as well. In future works, we study the performance and effectiveness of the proposed method on dynamic data found on more complex outlier removal algorithm found on the machine learning and deep learning algorithms [36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the performance of our proposed algorithm was evaluated on static data as well. In future works, we study the performance and effectiveness of the proposed method on dynamic data found on more complex outlier removal algorithm found on the machine learning and deep learning algorithms [36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is possible that the presented algorithm cannot find some global extrema. Therefore, we can use this algorithm along with GA or unsupervised learning models [36] to solve it for future studies. In the future, we first consider a solution to the problem with the Best-Fit algorithm presented in this study.…”
Section: The Time Complexitymentioning
confidence: 99%
“…On the other hand, there are some approaches to predict BTC price based on Natural Language Processing (NLP) and sentiment analysis. Today, NLP as an AI (artificial intelligence) technology and Deep learning [9,2] are used together in advanced text mining/analytic tools [23,4,26,8,7]. These approaches get social media text data from Twitter, Facebook, and etc., as the input and try to draw a link between the content of daily messages and the BTC price.…”
Section: Introductionmentioning
confidence: 99%